Achilles tendon re-rupture proximal to the primary repair in a collegiate football punter - Poole, C. M.; O`Connor Sutherland, A. C.; Martin, B. M.; Clanton, T. O. (Journal of Athletic Training, 2019)
Background: Achilles tendon ruptures typically present in males between the ages of 30-50 years-old, who participate irregularly in physical activity. This Level 3 CASE study falls outside of the normal age and level of physical activity demographic. In general, re-rupture rates of 1.7-5.6% are experienced following surgical management, while higher re-rupture rates of 11.7-20.8% are associated with conservative management. Patient: The patient is a 22 year-old male, Division I collegiate football punter, fi ve months following a right Achilles tendon repair using the Percutaneous Achilles Repair System (PARS) technique. He was progressing well with rehabilitation per protocol, when the patient experienced a "pop" followed by pain in his right Achilles tendon while performing agility drills. After initial clinical evaluation by the athletic trainer and head team physician, an MRI was obtained showing a complete rupture of the Achilles tendon approximately two centimeters proximal to the previous repair site. Due to the unique re-rupture location, the head team physician referred the patient for further evaluation. Four additional orthopaedic surgeons were consulted before the patient selected a treatment approach. Intervention or Treatment: Having been evaluated by fi ve different orthopaedic surgeons, variations of surgical techniques and non-operative management were discussed. The patient eventually underwent an open PARS revision with an Achilles Midsubstance SpeedBridgeTM technique two weeks following re-rupture. A sural nerve decompression and posterior compartment decompression fasciotomy were also performed. The patient was placed in a posterior stirrup splint in plantarfl exion for 10 days following surgery. He was then transitioned into a plantarfl exion short leg walking cast for an additional six weeks. Seven weeks following revision, the patient was then converted into a walking boot with three, half inch heel lifts. The patient began rehabilitation under the guidance of his athletic trainer. Controlled AROM exercises were initiated following cast removal, including AROM up to neutral dorsifl exion. Passive dorsifl exion ROM was initiated 10 weeks following surgery. In addition to the strengthening and ROM rehabilitation program, the patient concurrently began a four week weight-bearing progression, followed by a two week boot-wean after cast removal. He was also permitted to begin generalized strengthening and conditioning activities. Outcomes or Other Comparisons: The presentation of an Achilles tendon re-rupture fi ve months following surgery is highly unusual, with a paucity of literature and anecdotal evidence from physicians highly experienced in treating Achilles tendon ruptures. Furthermore, the rupture site proximal to the previous injury is particularly unusual. The highest rates of Achilles tendon re-ruptures typically occur between 6-8 weeks post-operatively and routinely transpire at the site of the previous rupture. Only one other report in the English literature has described an Achilles tendon re-rupture proximal to the initial repair site; however, the previously reported case did not include an elite athlete, as in this case. Conclusions: It is unclear exactly why a young, high level athlete experienced an Achilles tendon re-rupture proximal to the initial repair. No identifi able cause or pathology was found to be associated with this re-injury. Two months following surgery, the patient is progressing well with rehabilitation under the supervision of his athletic trainer, with the goal of participating in football next season. It is essential for athletic trainers to be knowledgeable of Achilles tendon re-rupture management strategies. Failure to recognize and appropriately treat Achilles tendon re-ruptures can impede the rehabilitation progress, lead to a decreased level of sports participation and may lead to permanent disability. Clinical Bottom Line: The objective of this case study is to educate athletic trainers regarding the presentation, surgical management and rehabilitation of a rare case of a late Achilles tendon re-rupture proximal to the primary repair in a collegiate football punter.